2012
DOI: 10.2175/193864712811709742
|View full text |Cite
|
Sign up to set email alerts
|

Mainstream partial nitritation/anammox: Balancing overall sustainability with energy savings

Abstract: Implementation of one-stage nitritation/anammox (i.e. deammonification) for the treatment of sludge digestates allowed net energy positive operation in the wastewater treatment plant (WWTP) in Strass (Austria). To further optimize the overall energy efficiency a first trial to expand the deammonification process to the full-plant wastewater treatment system was performed. The effluent quality, greenhouse gas emissions, energy balance and overall CO 2 footprint before and after implementation of mainstream DEMO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 15 publications
(20 reference statements)
0
2
0
Order By: Relevance
“…The differential in AOB and NOB rates can be obtained by for example operation close to washout sludge retention time of AOB and cyclic oxic-anoxic conditions (Regmi et al, 2014;Wett et al, 2012) and is a prerequisite of the success of the novel mainstream processes partial nitritation/anammox (PN/A) (Kuai and Verstraete, 1998). However, an AOB/NOB activity differential (specifically, owing to relatively lower NOB activity) and thus nitrite accumulation often results in increased nitrous oxide (N 2 O) and nitric oxide (NO) emissions (Chandran et al, 2011;De Clippeleir et al, 2012;Kampschreur et al, 2009). The similarity in conditions allowing for an AOB/NOB activity differential and NO/N 2 O emissions is remarkable (De Clippeleir et al, 2013) and raised the question if the emissions are a mere result of the nitrite accumulation after establishment of NOB out-selection or if the emissions can play a role in the NOB out-selection itself.…”
Section: Introductionmentioning
confidence: 99%
“…The differential in AOB and NOB rates can be obtained by for example operation close to washout sludge retention time of AOB and cyclic oxic-anoxic conditions (Regmi et al, 2014;Wett et al, 2012) and is a prerequisite of the success of the novel mainstream processes partial nitritation/anammox (PN/A) (Kuai and Verstraete, 1998). However, an AOB/NOB activity differential (specifically, owing to relatively lower NOB activity) and thus nitrite accumulation often results in increased nitrous oxide (N 2 O) and nitric oxide (NO) emissions (Chandran et al, 2011;De Clippeleir et al, 2012;Kampschreur et al, 2009). The similarity in conditions allowing for an AOB/NOB activity differential and NO/N 2 O emissions is remarkable (De Clippeleir et al, 2013) and raised the question if the emissions are a mere result of the nitrite accumulation after establishment of NOB out-selection or if the emissions can play a role in the NOB out-selection itself.…”
Section: Introductionmentioning
confidence: 99%
“…The importance of nitrite sensors measurements in side stream applications was demonstrated by investigators at the Strass, Austria WWTP who showed that there was a significant potential of reducing greenhouse gas emissions from anammox reactors if nitrite concentration could be controlled in the liquid phase (De Clippeleir et al, 2012;Lemaire et al, 2011).…”
Section: Introductionmentioning
confidence: 99%